Vivax malaria: a possible stumbling block for malaria elimination in India - Ashwani Kumar; Puspendra Pal Singh; Suchi Tyagi; K. Hari Kishan Raju; Sudhanshu S. Sahu; Manju Rahi; Manju Rahi (Frontiers Media S.A., 2024)
Plasmodium vivax is geographically the most widely dispersed human malaria parasite species. It has shown resilience and a great deal of adaptability. Genomic studies suggest that P. vivax originated from Asia or Africa and moved to the rest of the world. Although P. vivax is evolutionarily an older species than Plasmodium falciparum, its biology, transmission, pathology, and control still require better elucidation. P. vivax poses problems for malaria elimination because of the ability of a single primary infection to produce multiple relapses over months and years. P. vivax malaria elimination program needs early diagnosis, and prompt and complete radical treatment, which is challenging, to simultaneously exterminate the circulating parasites and dormant hypnozoites lodged in the hepatocytes of the host liver. As prompt surveillance and effective treatments are rolled out, preventing primaquine toxicity in the patients having glucose-6-phosphate dehydrogenase (G6PD) deficiency should be a priority for the vivax elimination program. This review sheds light on the burden of P. vivax, changing epidemiological patterns, the hurdles in elimination efforts, and the essential tools needed not just in India but globally. These tools encompass innovative treatments for eliminating dormant parasites, coping with evolving drug resistance, and the development of potential vaccines against the parasite.